Credibile ut intelligibile in St. Bonaventure's Commentary on the Sentences - Arosio, Marco (Ricerche di storia della filosofia e teologia medioevali, 2025)
This volume presents, for the first time in English, Marco Arosio’s study of Bonaventure’s theological epistemology: Credibile ut intelligibile. In this work Arosio seeks to clarify what Bonaventure meant when discussing theology as a science. The credibile is that which a Christian accepts by faith. The subject of theology, for Bonaventure, is the credibile insofar as reason makes it intelligibile, that is, something the rational mind understands. Reason applied to the credibile does make theology a scientia specialis, but it is a scientia specialis de omnibus. The theologian, whose concern is with the Bible as interpreted by the Fathers, is not limited by rules of deductive procedure, but embraces the knowledge of all things with the goal of ecstatic rapture. For Bonaventure, theology cannot be a merely rational process. Rather, the science of theology requires elevating grace and engages both intellect and will.